RELASI KAPITALIS TERIGU GLOBAL/INDOMIE DENGAN WARUNG WARMINDO DI DIY - Rini Admiwati; Yogawati, Irvan Dhani Prabowo, Sugiyanto (Jurnal Ekonomi dan Bisnis, 2024)
PT Indofood and Warmindo are more commercial than collaborative, without much direct interference or influence from the government. On the international stage, Indomie's popularity has attracted global attention, where Indomie has become a global symbol of Indonesian instant food. This shows how local products can achieve international recognition. This research is a relevant library source from primary data sources of previous research (research result data, research reports, scientific journals, etc.), which are relevant to this research. The research results show that Warmindo's business strength lies in its local community network and unique culinary appeal, which has allowed them to develop despite minimal direct support from the government. In conclusion, the government does not play much of a role in the Warmindo business in Yogyakarta and the existence of the Warmindo business is also supported by global wheat capitalism